2024
DOI: 10.1146/annurev-med-052422-020909
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects of Wildfire Smoke Exposure

Carlos F. Gould,
Sam Heft-Neal,
Mary Johnson
et al.

Abstract: We review current knowledge on the trends and drivers of global wildfire activity, advances in the measurement of wildfire smoke exposure, and evidence on the health effects of this exposure. We describe methodological issues in estimating the causal effects of wildfire smoke exposures on health and quantify their importance, emphasizing the role of nonlinear and lagged effects. We conduct a systematic review and meta-analysis of the health effects of wildfire smoke exposure, finding positive impacts on all-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“…Climate changes related to temperature, humidity, and drought are associated with increased frequency, duration, and severity of wildfires in many countries. 1,2 Recent major wildfires include those in the US (2017-2023), Australia (2019-2020), Canada (2023), Greece (2023), Russia (2021), the Amazon rainforest (2019), and Bolivia (2010). Each year, approximately 44 million people are exposed to unhealthy air quality due to wildfires worldwide.…”
Section: Background On Wildfires and Air Pollutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Climate changes related to temperature, humidity, and drought are associated with increased frequency, duration, and severity of wildfires in many countries. 1,2 Recent major wildfires include those in the US (2017-2023), Australia (2019-2020), Canada (2023), Greece (2023), Russia (2021), the Amazon rainforest (2019), and Bolivia (2010). Each year, approximately 44 million people are exposed to unhealthy air quality due to wildfires worldwide.…”
Section: Background On Wildfires and Air Pollutionmentioning
confidence: 99%
“…Each year, approximately 44 million people are exposed to unhealthy air quality due to wildfires worldwide. 2 Although fire patterns vary year to year, meteorological data on wildfires have demonstrated that worldwide, people experienced 6 more days of high fire danger on average from 2018 to 2022 compared with 2003 to 2007, and this exposure is projected to increase by 9 extra days per person (an 11% increase) by 2050. 3 Since 1985, land burned by wildfires in the US each year has increased from approximately 1 million hectares (3900 square miles; ~6276 km) to more than 3 million hectares (11 500 square miles; ~18 507 km).…”
Section: Background On Wildfires and Air Pollutionmentioning
confidence: 99%
“…Wildfire PM 2.5 can infiltrate the lungs and precipitate respiratory events through inflammation and oxidative stress (Xing et al, 2016). In previous epidemiological studies, exposure to wildfire smoke has been linked to a variety of adverse health effects, particularly for respiratory conditions (Aguilera et al, 2020(Aguilera et al, , 2021Gould et al, 2024;Kondo et al, 2019;Reid & Maestas, 2019). Recent toxicologic and epidemiologic studies found that wildfire PM 2.5 can have a higher adverse health impact on the pulmonary system than PM 2.5 from other sources (Aguilera et al, 2021;Kim et al, 2018;Wegesser et al, 2009), and disregarding the differential dose-response of wildfire PM 2.5 led to an underestimation of PM 2.5 related health burden (Darling et al, 2023), which warrants independent studies of wildfire PM 2.5 health impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the health effects of wildland fire exposure predominantly focused on the effects of short-term exposure, typically examining exposure periods within one or two weeks. Most studies reported a positive relationship between short-term wildland fire smoke exposure and all-cause mortality (9, 1113). A growing number of studies linked short-term exposure to wildland fire smoke to increased risks of respiratory mortality and presented mixed evidence regarding cardiovascular mortality (1114).…”
Section: Introductionmentioning
confidence: 99%